2016
DOI: 10.7554/elife.18491
|View full text |Cite
|
Sign up to set email alerts
|

Viral factors in influenza pandemic risk assessment

Abstract: The threat of an influenza A virus pandemic stems from continual virus spillovers from reservoir species, a tiny fraction of which spark sustained transmission in humans. To date, no pandemic emergence of a new influenza strain has been preceded by detection of a closely related precursor in an animal or human. Nonetheless, influenza surveillance efforts are expanding, prompting a need for tools to assess the pandemic risk posed by a detected virus. The goal would be to use genetic sequence and/or biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 240 publications
(342 reference statements)
0
95
0
1
Order By: Relevance
“…Although the true number of human cases, and hence accurate mortality, is difficult to ascertain, it is clear that both H5N1 and H7N9 cause fairly high mortality in humans and could have serious consequences were they to trigger a large-scale human epidemic. This concern has led to attempts to use genomic data to help in pandemic risk assessment 80 .…”
Section: Avian Influenza a Virusmentioning
confidence: 99%
“…Although the true number of human cases, and hence accurate mortality, is difficult to ascertain, it is clear that both H5N1 and H7N9 cause fairly high mortality in humans and could have serious consequences were they to trigger a large-scale human epidemic. This concern has led to attempts to use genomic data to help in pandemic risk assessment 80 .…”
Section: Avian Influenza a Virusmentioning
confidence: 99%
“…Avian influenza viruses α-2,6-linked sialic acid receptor Mutations in receptor binding site of viral HA One or a combination of mutations in HA is required; several different combinations have been observed [61][62][63] ANP32A host cofactor for the viral polymerase…”
Section: Viral Mutations That Overcome Barrier Amentioning
confidence: 99%
“…Yet the limited generalizability of GOF research to the surveillance of currently circulating strains supports the need for further research into universal predictors of pandemic emergence. Alternative approaches to pandemic risk modelling have been proposed which are worth exploring, such as identifying molecular determinants of HA evolution . For example, studies have shown the protein structure of avian HA partially determines the mutation rate within the RBS and thus, greater opportunities for selection towards human respiratory cells, increasing risk .…”
Section: Resultsmentioning
confidence: 99%
“…Alternative approaches to pandemic risk modelling have been proposed which are worth exploring, such as identifying molecular determinants of HA evolution. 66 For example, studies have shown the protein structure of avian HA partially determines the mutation rate within the RBS and thus, greater opportunities for selection towards human respiratory cells, increasing risk. 67,68 Additionally, investing in greater diagnostic capacity to support surveillance systems, improving response plans for non-pharmaceutical interventions and stockpiling antivirals and PPE are equally important during both the pre-and early pandemic phases.…”
Section: Discussionmentioning
confidence: 99%